Clinical Features and PTCH1 Expression in Gorlin–Goltz Syndrome: A Case Report - Gabriela González-López; Samuel Mendoza-Álvarez; Claudia Patricia Mejia-Velazquez; Carla Monserrat Ramírez-Martínez; Alejandro Alonso-Moctezuma; Luis Fernando Jacinto-Alemán (Reports)
Background and Clinical Significance: Basal cell nevoid carcinoma syndrome, or Gorlin–Goltz Syndrome (GGS), is a genetic disease caused by germline mutations in genes involved in the Sonic HedgeHog (SHH) signaling pathway, mainly in the PTCH1 gene. PTCH1 is a receptor for SHH, and the activation of SHH signaling exerts a direct effect on the proliferation and maintenance of stem cells; alteration of its signaling could promote a favorable microenvironment for the maintenance of tumor viability. The main clinical manifestations of patients with GGS include multiple basal cell carcinomas, odontogenic keratocysts, calcification of the falx cerebri, palmoplantar fossae, hypertelorism, prognathism, fused or bifid ribs, and macrocephaly, which occur at different stages of life. Case Presentation: Here, the case of a 48-year-old woman is described, for whom a clinical and histopathological diagnosis of GGS was made due to the presence of two major criteria (multiple odontogenic keratocysts and calcification of the falx cerebri) and one minor criterion (congenital anomalies), according to Kimonis. Additionally, an end-point RT-PCR assay showed a decrease in PTCH1 gene expression. A conservative therapy was established, and satisfactory results were obtained in a follow-up period of 18 months. Conclusions: Kimonis' clinical criteria are important for establishing the diagnosis of Gorlin syndrome.